Diseño de un prototipo de sistema de control y gestión de recursos humanos y seguridad como soporte a la toma de decisiones basados en sistemas biométricos - Anormaliza Farfán, Danny (2011)
This document aims to implement a control and security assistance in what refers to access employees to deferent areas of a business or home by a biometric reader. Biometric systems in recent years have grown to become an important tool to support existing security systems, as scientific advances in the field of fingerprint identification, face recognition, voice recognition and others. Biometric systems are used for the recognition of a unique feature of a person, usually consisting of components of both hardware and software required for the recognition process. The new security technologies rely on human traits rather than passwords (passwords) or physical documents. Short passwords are easily compromised. Control System and Human Resources Management and security based on biometrics, will control entrance and exit of personnel, and reducing the time for obtaining and generating the required information (detail of hours worked, income and outputs personnel, etc.), prevent identity theft in the event logs of the staff, which reduces administrative costs.